The effect of exercises in the third intensity zone of the strength characteristic of the speed of the two legs on the adequacy of the circulatory and respiratory systems and the performance of some basketball skills among young players - Khalaf , Zainab (Journal of Physical Education, 2024)
The research aimed to prepare exercises area intensity third strength distinctive speed of the two men for young players basketball, and to identify its impact on the adequacy of the circulatory and respiratory systems and in the performance of some of their basketball skills, and the researcher assumed that there are statistically significant differences between the results of the pre- and post-tests of the experimental and control research groups for each of the adequacy of the circulatory and respiratory systems and the performance of some basketball skills, and there are statistically significant differences between the results of the tests of the experimental research groups and the dimensional control for each of the adequacy of The circulatory and respiratory systems and the performance of some basketball skills, and the experimental approach was adopted by designing the experimental and equal control groups, on a sample of (12) players who were deliberately selected by (75%) of the young basketball players at the Industry Sports Club for the season (2022-2023), and after determining the tests and preparing the exercises, they were applied over a period of (10) consecutive weeks at a rate of two units per week, and after the completion of the experiment, the results were processed with the (SPSS) system to be the conclusions that the application of the exercises of the third intensity zone of the strength characteristic of the speed of the two men helps in developing the adequacy of the circulatory and respiratory systems, and in improving the performance of some skills among young basketball players, and the researcher recommended that, it is necessary to adopt the application of intensity area exercises The third is for the strength characterized by the speed of the two men for the young players in basketball and the good rationing of the high-intensity training load without exaggerations, It is necessary to pay attention to developing the capabilities of basketball coaches when working on the application of exercises in the third intensity zone of strength characteristic of speed for the two men for young basketball players that aim to develop their physiological skill factor.